IMPLEMENTATION OF FILM THERAPY TO PREVENT BULLYING BEHAVIOR IN CLASS VIII STUDENTS OF SMPN 2 KABAT - Miftahul Arifin; Ria Agustina; Tofan Priananda Adinata (International Jurnal of Education Schoolars, 2021)
Ria Agustina, 2021; Implementation of Film Therapy for the Prevention of Bullying Behavior in Class VIII Students of SMPN 2 Kabat.50 pages; Counseling Guidance Study Program, Faculty of Teacher Training and Education, PGRI University Banyuwangi. Supervisor: (I) Heriberthus Wicaksono, M.Pd., Psi (II) Tofan Priananda Adinata, M.Sc. Seeing how bad the impact caused by bullying behavior is, the researchers conducted research to resolve and prevent bullying behavior in schools by using film therapy techniques to make it easier for researchers to provide students with an understanding of the dangers of bullying behavior. Film therapy is a technique that uses films to get the meaning of the process of guidance and counseling to the counselee regarding the ability to see oneself or other individuals. The purpose of this study was to determine whether the use of film therapy can be used to prevent bullying behavior. The approach used in this research is a quantitative approach, using one type of method from the type of descriptive research. Descriptive quantitative is a type of research that is used to analyze data by describing or describing the data that has been collected as it is. Based on the results of the analysis of the one sample t test with a significance value of 0.00, after being compared with the t significance level of 0.05, it is concluded that this study rejects Ho and accepts Ha. The researcher concludes that film therapy can be applied in preventing bullying behavior in seventh grade students of SMPN 2 Kabat.